Antropologi Suku Bugis - Selfia Agustina; Moch Iqbal; Ismail Ismail (DAWUH : Islamic Communication Journal, 2024)
This article highlights the anthropology of the Bugis tribe by getting to know the beginnings of the Bugis tribe, the customary legal system, language and script, marriage, religious systems, the mental and character of the Bugis tribe and the title of nobility. The method used in this research is a qualitative literature study from several book and journal sources collected to examine information related to the lives of the Bugis-Makass tribe. This research produces various information related to the lives of the Bugis-Makassar tribe, from which we know that the Bugis-Makassar tribe is one of the unique tribes in Indonesia with its ties of customs, culture and social life. In this journal, the caste/national title system of the Bugis tribe is also provided, which is still upheld by the Bugis-Makassar people to this day.